Catalytic selective hydrogenation of acetic acid to acetaldehyde over the surface of the iron shell on Pd–Fe alloy nanoparticles. Issue 18 (4th August 2022) - Hosokawa, Saburo; Fukuzumi, Noriyuki; Nakatani, Tetsu; Honma, Tetsuo; Mizugaki, Tomoo; Tanaka, Tsunehiro; Wada, Kenji
Abstract : The Fe metal shell on Pd–Fe alloy nanoparticles formed by strong metal–support interaction (SMSI) promotes catalytic selective hydrogenation from acetic acid to acetaldehyde. Abstract : Since hydrogenation of acetic acid readily leads to ethanol formation, it is challenging to selectively obtain acetaldehyde in a high yield. The present study demonstrates the highly-selective synthesis of acetaldehyde by the hydrogenation of acetic acid catalyzed by the iron surface on Pd–Fe alloy nanoparticles derived from Pd/Fe2 O3 . The catalyst from Pd/Fe2 O3 with low Pd loading amount provoked the deposition of carbonaceous species, including iron carbides, in the prolonged reaction, resulting in a low acetaldehyde yield. On the contrary, Pd/Fe2 O3 with high Pd loading amount (28–44 wt%) prevented the formation of iron carbides. It led to the formation of aldehyde in an excellent yield, that was maintained even after 200 h. Further Pd loading increased the ethanol formation. In situ XAFS measurements showed that the reductive pretreatment under hydrogen flow of Pd/Fe2 O3 formed the core–shell type Pd–Fe alloy nanoparticles. Acetic acid would convert to acetaldehyde with concomitant oxidation of the surface of the metallic iron shell, and H2 would reduce the thus-partially oxidized shell to regenerate the initial metallic surface.